Spatiotemporal heterogeneities and drivers of air pollution in Chinese megacity: a case study of Chengdu - Xiong, Xin; Qiu, Jianhong; Zhao, Rui; Du, Pengbo; Zhao, Liping (Frontiers in Environmental Science, 2025)
IntroductionThe rapid urbanization and industrialization, accompanied by high-intensive population, energy consumption and transportation activities, have made air pollution an intractable environmental issue in China, especially in most megacities. This study identified the primary air pollutant (PAP) of a Chinese megacity—Chengdu, and analyzed the spatiotemporal changes of PAP concentrations.MethodsThe LMDI and GWR models were employed to probe the spatiotemporal drivers of air pollution in Chengdu.Results and discussionThe pollutants of PM10, PM2.5, O3, and NO2 were identified as the PAPs of Chengdu. During the period of 2015∼2021, the concentrations of the four PAPs showed decreasing trends from 90.5 μg/m3, 56.7 μg/m3, 90.0 μg/m3, and 34.0 μg/m3 to 54.2 μg/m3, 33.7 μg/m3, 87.0 μg/m3, and 29.1 μg/m3, respectively. In 2021, the spatial distributions of the PAP concentrations were characterized by being higher in the central areas. The temporal changes in the PAP concentrations were conjointly influenced by population, per capita GDP, urban built-up area per unit GDP, greenery coverage rate, and pollution load intensity of greenery, with positive effects of population, per capita GDP, and greenery coverage rate and negative effects of urban built-up area per unit GDP and pollution load intensity of greenery. In spatial, the geographical factors (including temperature, precipitation, wind speed, cultivated area and vegetation coverage rate) and socio-economic factors both affected the PAP concentrations. However, there were spatial heterogeneities in the driving forces between different districts of Chengdu, due to the disparities in both the socio-economic and geographical context in different areas. This study also highlights possible policy implications for alleviating urban air pollution, and provides scientific insights for building the clean and livable urban environments for cities.